Food safety in the home consumption of meat in Turkey - Karabudak, Efsun; Bas, Murat; Kiziltan, Gul (Food control, 2008)
In this study, we investigated consumer meat-handling practices in Turkey. We conducted face-to-face interviews with 1090 consumers who included meat in their diet and were the primary shopper and food handler in their home. The subjects also completed a questionnaire about their meat-handling practices. We found that many of those individuals failed to store meat at the correct temperature or did not correctly defrost meat. Food-handling practices varied according to the socioeconomic group and level of education of the respondent, and gaps in food safety knowledge were noted. Turkish meat consumers must be informed about the safe handling of meat products to prevent foodborne illness and ensure optimal food safety.